Baroque Aspects in the Poetics of Victor Pelevin - Ченис, Томас (Literatūra, 2017)
This article aims to reveal and describe some of the features of the poetics of Victor Pelevin. As a working hypothesis, an idea is suggested that Pelevin takes some distance from the postulates of classical postmodernism and uses the aesthetic notions and techniques of the Baroque. Thus, Pelevin’s work is to be regarded in the context of the poetics of baroque, which should be separated from the Neobaroque of postmodernism. Neo-baroque is regarded in two aspects – as one of the components of postmodernism, and even beyond this trend, when some elements, like its theatricality or the contrasts, being baroque, can go beyond postmodernism. The two main texts analyzed in this framework are Chapayev and Void and Pineapple Water for the Fair Lady. In the article, theatricality is shown to be not only used to make the style of works more striking on the reader, but that it also has a didactic nature in that it gives the author means to show his position through the performance. Baroque contrasts structure the narrative, making heroes escape from the illusionary and chaotic world described in books of Viktor Pelevin. BAROKINIAI ASPEKTAI VIKTORO PELEVINO POETIKOJE Straipsnyje keliamas tikslas atskleisti barokinius Viktoro Pelevino kūrybos poetikos bruožus. Keliama hipotezė, kad autoriaus tolsta nuo postmodernizmo postulatų ir naudoja baroko estetines idėjas ir stilistines priemones. Šios hipotezės kontekste, galima kelti klausimą, kiek Pelevino kūryba priklauso postmodernizmui būdingai neobaroko srovei. Neobarokas straipsnyje interpretuojamas kaip postmodernizmo ir aspektų, išeinančių už postmodernizmo ribų, tokių kaip teatrališkumas ir kontrastai, visuma. Pelevino tekstų – romano „Čapaevas ir Pustota“ bei apsakymų rinkinio „Ananasinis vanduo puikiajai damai“ – analizė atskleidžia, kad autoriaus tekstų teatrališkumas yra ne tik meninė priemonė, bet ir būdas atskleisti didaktinę Pelevino intenciją ir suteikia jam galimybę išsakyti savo nuomonę. Tuo tarpu barokiniai kontrastai tokiu būdu struktūruoja pasakojimą, kad herojams suteikiama galimybė pabėgti iš netikro, chaotiško pasaulio, kurią kuria Viktoras Pelevinas.